Renewed roles in the History of Medicine - Armocida, Giuseppe (Medicina Historica, 2017)
In the last decades, medicine has really achieved extraordinary healing skills, almost unimaginable once. But the refined model we use has not yet been able to give convincing explanations about the aggressiveness of many pathologies that remain mysterious as far as etiology is concerned. Science produces exciting successes, but there are still many gaps between what we expect from medicine and how much it can offer. [...]